The Effect of Work Discipline, Compensation, and Work Environment on Employee Performance at PT. Pembangunan Teknik Konstruksi - Rusman Nopriady Rahman; Mulyana Mahcmud; Irmayanti Sudirman; Bakhtiar Tijjang; Safrida (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the effect of work discipline, compensation, and work environment on employee performance at PT. Pembangunan Teknik Konstruksi. This research employs a quantitative approach using SPSS version 27 for data analysis. Data were collected through questionnaires, interviews, literature review, and documentation. The population in this study consisted of 103 employees, and the sampling technique used was saturated sampling, resulting in 103 respondents. The results of the study indicate that partially, work discipline has a positive and significant effect on employee performance, and compensation also has a positive and significant effect on employee performance. Meanwhile, the work environment does not have a significant effect on employee performance. Simultaneously, work discipline, compensation, and work environment have a significant effect on employee performance. The findings of this study reveal that work discipline and compensation are the dominant factors in improving employee performance, while the work environment is not the main factor in this research context. Therefore, the company is recommended to focus more on enhancing work discipline and providing fair and appropriate compensation to improve employee performance optimally